Interdisciplinary and Multidisciplinary Issues, Challenges and Opportunities for Developing Cash Waqf - Indah Rofiqoh, Siti Nur; Ratnasari, Ririn Tri; Fadlillah, Nilna; Sulistyowati, Sulistyowati; Habibah, Aminatun (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This paper undertakes a survey of the case studies and literature review on cash waqf. The aim is to provide an understanding of the issues, challenges, and potential opportunities for developing cash waqf by SWOT-LISA analysis. Our survey reveals that three is a need to: (a) focus on new development program, including riil market sector, (b) establish the cash waqf statistical datasets, and (c) establish the robustness of the cash waqf finding.